Prognostic significance of muscle fasciculations in critically Ill COVID-19 patients under mechanical ventilation - Molinger, Jeroen; Whittle, John; Cha, Susie; MacLeod, David; Fudim, Marat; Ulloa, Luis; Barkauskas, Christina; Healy, Zachary; Haines, Krista L.; Gupta, Rajan T.; Endeman, Henrik; van der Jagt, Mathieu; et al. (Frontiers in Anesthesiology, 2024)
Introduction The COVID-19 pandemic brought unprecedented challenges to healthcare systems worldwide, particularly the often challenging physical recovery from critical illness. Among the myriad complications faced by these patients, ICU-acquired weakness (ICU-AW) stands out due to its significant impact on patient outcomes. ICU-AW, characterized by skeletal muscle atrophy and weakness, is linked to critical illness polyneuropathy (CIN), myopathy (CIM), and muscle atrophy. Notably, fasciculations, or involuntary muscle twitches, have been observed in patients with ICU-AW, suggesting altered muscle fiber excitability. This study aimed to describe the pattern of fasciculations in critically ill mechanically ventilated COVID-19 patients, assess clinical features associated with fasciculations, and evaluate their prognostic significance. Methods The study enrolled patients admitted to the Intensive Care Unit (ICU) with COVID-19 infection requiring intubation and mechanical ventilation. Quadriceps muscles were assessed using muscle skeletal (MSK) ultrasound and Phase Angle (PhA) through multifrequency segmental bioelectrical impedance analysis (MFBIA) every 72 h. PhA is considered a marker of cell membrane integrity and function, with lower PhA values indicating reduced skeletal muscle quality and increased risk of sarcopenia. Fasciculations were classified based on their appearance and frequency. Results A total of 35 intubated patients were studied, with 15 patients (43%) displaying scattered fasciculations exclusively in the vastus intermedius muscles. Upon admission, the study found no significant difference in PhA between the fasciculation and non-fasciculation groups. However, PhA decreased significantly from admission to discharge ICU only in the fasciculation group. Patients with fasciculations exhibited higher mortality rates, though not statistically significant, and this correlated with prolonged ICU and hospital lengths of stay. Discussion This study is the first to report scattered fasciculations in the vastus intermedius muscles of multiple patients with SARS-CoV-2 infection identified with MSK ultrasound. The findings suggest that the combination of impaired muscle cellular function (PhA) and the onset of fasciculations could serve as a potential biomarker of adverse outcomes and ICU-related muscle dysfunction and muscle loss.